(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассматриваются вопросы трансформации объектно-предметной сущности, теории и методологии социально-экономической географии в условиях формирования новой научной картины мира и появления человека в контексте синергетической самоорганизации Вселенной. Ставится центральная проблема географии – создания общей теории ландшафтной оболочки Земли. Приведены пути внедрения общественно-географических исследований в практику регионального и социально-экономического развития Украины. METHODOLOGIC PROBLEMS AND TRANSFORMATIONS IN MODERN SOCIAL AND ECONOMICAL GEOGRAPHY The article concerns the questions of transformation of human geography’s object and subject, its theory and methodology in the conditions of new world scientific picture’s forming and human displaying in context of the Universe’s synergetic self-organization. The problems of main geographical question – creation of common theory of the Earth’s landscape sphere – are revealed. It is described the ways of using human geographical researches in the practice of regional and socio-economical development of Ukraine.